Food chain frenzy - Capeci, Anne.; Speirs, John (New York : Scholastic, 2003)
Arnold and his classmates are whisked away on an adventrue when they study the food chain.
"Based on The Magic School Bus books written by Joanna Cole and illustrated by Bruce Degan"--T.p. verso.
610
Accelerated Reader AR
Keywords: Schools -- Juvenile fiction